Liberation and the aims of science : - Easlea, Brian (Chatto & Windus for Sussex University Press, 1973)
Chapter 1. Objectivity and commitment in the physical sciences; Chapter 2. The copernican Revolution: a study of paradigms and commitments; Chapter 3. The breakdown of the Newtoian paradigm: a study of Crisis; ... ...